Environmental DNA helps reveal reef shark distribution across a remote archipelago - Nicholas Dunn; David J. Curnick; Chris Carbone; Aaron B. Carlisle; Taylor K. Chapple; Rosalie Dowell; Francesco Ferretti; David M.P. Jacoby; Robert J. Schallert; Margaux Steyaert; David M. Tickler; Michael J. Williamson; et al. (Ecological Indicators, 2023)
Environmental DNA (eDNA) methods are being increasingly used in proof-of-concept studies to detect shark species, many populations of which are experiencing severe declines. These methods are widely seen as the future of biodiversity monitoring, but they have yet to become established as routine monitoring techniques for elasmobranch species. Here, we developed species-specific quantitative PCR assays for the detection of grey reef shark (Carcharhinus amblyrhynchos) and silvertip shark (Carcharhinus albimarginatus). We assessed whether species-specific eDNA methods could infer the distribution of the two species around the atolls of the Chagos Archipelago, which, despite being surrounded by a large marine protected area, experience contrasting levels of illegal fishing leading to heterogeneity in shark population densities. We found that eDNA detections were significantly reduced and sporadic around the northern atolls, which are under high pressure from illegal fishing. By contrast eDNA detections of both species were ubiquitous and consistent around the highly protected atoll Diego Garcia. We postulate that current levels of illegal, unreported and unregulated (IUU) fishing is having a significant impact on the shark community in the northern atolls and suppressing local reef shark populations. In the northern atolls we also employed visual and acoustic telemetry techniques to reveal the distribution of reef sharks. We found that despite eDNA samples being taken directly after visual surveys, detection results did not correlate, suggesting a need for further optimisation of eDNA methods for detecting sharks. However, both species were detected by eDNA in sites where they were not observed, highlighting that the scale of the sampling environment must be considered when inferring eDNA results and showing that eDNA methods can be used to fill gaps in data from more established monitoring techniques. We conclude that eDNA methods should be used in combination with other techniques to provide a complete picture of shark distribution so that threatened species can be better protected.